A case of carcinoma of the hepatic hilus occuring 3 years after the operation for hepatolithiasis and pancreatolithiasis - MATSUMOTO, Mitsuyuki; SHIRAISHI, Masayuki; ISA, Tsutomu; MUTO, Yoshihiro; NAKAMOTO, Takeru; KUSANO, Toshiomi; ICUSHI, Kazuaki; NAKACHI, Atsushi; TAMAI, Osamu; YAMADA, Mamoru (Tando, 1995)
The patients was seventy-year-old female with carcinoma of the hepatic hilus occuring 3 years after the operation for hepatolithiasis and pancreatolithiasis. She underwent cholecytectomy, choledochotomr for hepatolithiasis and pancreaticojejunostomy for pancreatolithiasis in November,1991. She was discharged after the complete elimination of stone by the cholangioscopic lithotripsy with persistent dilatation of intra and extrahepatic bile duct. She was admitted to our hospital with complaints of fever, appetite loss and general fatigue about three years later. Percutaneous transhepatic cholangiography revealed filling defect of bile duct in the hepatic hilus and biopsy of the tumor through the cholangioscopy revealed adenocarcinoma. Resection of the extrahepatic bile duct was performed. Resected specimen showed nodular-type tumor at the left hepatic duct and its invasion to right hepatic duct. Histological examination revealed mucinous adenocarcinoma. This case indicated that resection of the involved segment of the liver and dilated bile duct on initial admission should be necessary because long-standing bile stasis and infection in dilated bile duct may induce the occurrence of carcinoma.